PENGARUH PERPUTARAN KAS, PERPUTARAN KREDIT DAN EFEKTIVITAS BADAN PENGAWAS PADA RENTABILITAS - Wahyudi, I Wayan; Eka Damayanthi, I Gusti Ayu (E-Jurnal Akuntansi, 2015)
LPD is a microfinance non-bank on Pakraman in Bali. Management of assets LPD can be seen in ability to organize of cash turnover, turnover credit and effectiveness of regulatory body can contribute to the profitability. The purpose of this study to determine the effect of cash turnover, turnover of credit, and effectiveness of the regulatory body for economic profitability LPD . This study using 102 samples, with a purposive sampling method. The data analysis technique used is multiple linear regression with first tested the classical assumption of, normality test, autocorrelation test, multikolinieratias test, and heteroscedasticity test. Based on the results of multiple regression analysis, it is known that the results showed level of cash turnover, turnover of credit, and the effectiveness of regulatory body partially significant effect on economic profitability LPD in Denpasar City.
Keywords: Turnover levels Cash, Credit Turnover, and effectiveness of the Supervisory Board, Economic Profitability